Some Pro and Anti-Inflammatory Cytokines in Children with Tonsillitis and their Correlations with Vitamin D Deficiency - Zainab Alhakeem; Najwan Kaisar Fakree; Ahmed AbdulSamad Muhsen; Nuha Majeed Hashim (College of Pharmacy University of Baghdad, 2022)
Inflammation of the tonsils could be described as acute tonsillitis, mainly due to infection. Recurrent tonsillitis could be defined as 3-7 episodes during the first 3 years of age. Vitamin D, which is a neuro-hormone with pleiotropic biological activities may modulate the immune response by alleviation, and stimulation of Th1 and Th2 cell proliferation, respectively, that influence the stimulation, synthesis, and secretion of both pro and anti-inflammatory cytokines. In this study we aimed to shed light on the levels of vitamin D in children with different episodes of tonsillitis in association with levels of interleukins (TNFα, IL-2, IL-4, IL-10). Blood samples were collected from 48 participants in 3 groups: control, acute tonsillitis (1-2 episodes/year), chronic tonsillitis (more than 7 episodes/year), serum was separated and the levels of Vitamin D, TNFα, IL-2, IL-4 and IL-10 were estimated using ELISA technique. Vitamin D decreased significantly as the episodes of tonsillitis increased, with level of 16.38± 2.41ng/ml in acute and, 14.13± 2.15 ng/ml in chronic tonsillitis as compared to control (30.91± 2.31 ng/ml), while pro-inflammatory cytokines (TNFα and IL-2) significantly increased (46.88± 14.05 and 44.55± 9.24, 1267.25± 111.85 and 1191.72± 121.52 ng/ml, respectively) as compared to control (9.45 and 138.48 ng/ml respectively). Anti-inflammatory (IL-4, IL-10) cytokines in control group were (243.08± 28.72 and 24.27± 1.83 ng/ml, respectively), which increased non-significantly in acute and chronic tonsillitis (302.76± 38.93, 290.12± 44.69 and 28.16± 2.01, 26.29± 1.99 ng/ml, respectively). Significant direct correlation was observed between the levels of vitamin D and anti-inflammatory cytokines in chronic tonsillitis (P<0.05). In conclusion, deficiency of vitamin D may affect the number of episodes of tonsillitis in children by modulation of the secretion of some cytokines.